Advanced Glycation End Products Enhance Murine Monocyte Proliferation in Bone Marrow and Prime Them into an Inflammatory Phenotype through MAPK Signaling. (22nd March 2018) - Jin, Xian; Liu, Liang; Zhang, Yaping; Xiang, Yin; Yin, Guizhi; Lu, Yi; Shi, Ludong; Dong, Jian; Shen, Chengxing
Abstract : Objective . Increased monocytes, particularly the inflammatory subset, are associated with accelerated atherosclerosis in diabetes through thus far incompletely defined mechanisms. The present study tested the hypothesis that advanced glycation end products (AGEs) promote bone marrow monocytes to proliferate and drive them into an inflammatory phenotype. Methods and Results . In vivo, AGEs (25 mg/kg i.p. for 7 days) increased proportions of CD115 + monocytes and the inflammatory subset, the CD115 + Ly6C high cells, in murine bone marrow (flow cytometry analysis (FCM)), and enhanced gene expression of proinflammatory cytokines (IL-1 β and TNF- α ) but only slightly upregulated mRNA expression of anti-inflammatory cytokine (IL-10) (real-time PCR) in monocytes. In vitro, when the monocytes were treated with different dosages of AGEs (50, 150, and 300 μ g/mL), we found that proliferation (CCK8) but not apoptosis (FCM) of the monocytes was induced; the mRNA expressions of proinflammatory cytokines (IL-1 β and TNF- α ) and GM-CSF were upregulated in a dose-dependent manner while mRNA levels of IL-10 and M-CSF were changed much less in monocytes (real-time PCR). Furthermore, AGEs (300 μ g/mL) significantly enhanced the expression of Ki67 in monocytes (immunofluorescence staining (IF)), and this dose of AGEs markedly increased secretion of GM-CSF but not that of M-CSF (ELISA). For a pathway study, the monocytes were stimulated by 300 μ g/mL AGEs for different periods of time (0, 15, 30, and 120 min) and the activation of the MAPK pathway was tested (FCM); the results showed the p38 and ERK pathways were activated but not JNK signaling. Pretreatment with an inhibitor of p38 (SB203580) or ERK (U0126) attenuated AGE-induced gene expression of proinflammatory cytokines and GM-CSF (real-time PCR), as well as reversing AGE-induced Ki67 expression (IF). Conclusions . AGEs promote bone marrow monocytes to proliferate and drive them into an inflammatory phenotype through p38 and ERK activation.